Polarity-Dependent High Electrical Conductivity of ZnO Nanorods and Its Relation to Hydrogen - Alex Lord (The Journal of Physical Chemistry C, 2018)
A statistical analysis of the electrical properties of selective area grown O- and Zn-polar ZnO nanorods by chemical bath deposition is performed by four-point probe resistivity measurements in patterned metal contact and multiprobe scanning tunneling microscopy configurations. We show that ZnO nanorods with either polarity exhibit a bulklike electrical conduction in their core and are highly conductive. O-polar ZnO nanorods with a smaller mean electrical conductivity have a nonmetallic or metallic electrical conduction, depending on the nano-object considered, while the vast majority of Zn-polar ZnO nanorods with a larger mean electrical conductivity present a metallic electrical conduction. We reveal, from Raman scattering and spatially resolved 5 K cathodoluminescence measurements, that the resulting high carrier density of ZnO nanorods with O or Zn polarity is due to the massive incorporation of hydrogen in the form of interstitial hydrogen in bond-centered sites (HBC), substitutional hydrogen on the oxygen lattice site (HO), and multiple O–H bonds in a zinc vacancy (VZn–Hn). While HBC is largely incorporated in ZnO nanorods with either polarity, HO and (VZn–Hn) defect complexes appear as the dominant hydrogen-related species in O- and Zn-polar ZnO nanorods, respectively. These findings reveal that polarity greatly affects the electrical and optical properties of ZnO nanorods. They further cast a light on the dominant role of hydrogen when ZnO nanorods are grown by the widely used chemical bath deposition technique. This work should be considered for any strategy for thoroughly controlling their physical properties as a prerequisite for their efficient integration into nanoscale engineering devices.